Antibacterial and antioxidant activities of essential oils isolated from Thymbra capitata L. (Cav.) and Origanum vulgare L. - Faleiro, Leonor (2015)
Antilisterial activities of Thymbra capitata and Origanum vulgare essential oils were tested against 41 strains of Listeria monocytogenes. The oil of T. capitata was mainly constituted by one component, carvacrol (79%), whereas for O. vulgare three components constituted 70% of the oil, namely, thymol (33%), gamma-terpinene (26%), and p-cymene (11%). T. capitata essential oil had a significantly higher antilisterial activity in comparison to O. vulgare oil and chloramphenicol. No significant differences in L. monocytogenes susceptibilities to the essential oils tested were registered. The minimum inhibitory concentration values of T. capitata essential oil and of carvacrol were quite similar, ranging between 0.05 and 0.2 mu L/mL. Antioxidant activity was also tested, the essential oil of T. capitata showing significantly higher antioxidant activity than that of O. vulgare. Use of T. capitata and O. vulgare essential oils can constitute a powerful tool in the control of L. monocytogenes in food and other industries.